Is lower back pain a growing issue in Pakistani adult population? - Ali Warsi, Syed Muhammad Farzan; Hasan, Zainab (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Low back pain (LBP) is not a disease itself, but it can be a sign of number of a number of conditions, such as pain near the midline, which can occasionally be localized sometimes, and occur between the inferior gluteal folds and costal margin, with or without referred leg pain [1,2]. The prevalence of LBP has been rising globally; According to recent studies Bangladesh, India, Nepal, Pakistan and Sri Lanka have rates of 64.8%, 19.8%, 69.5%, 40.6% and 36.2% respectively [3]. LBP can be categorised as either non-specific or specific. Non-specific means that the experience of pain cannot be confidently accounted for by another diagnosis such as an underlying disease, pathology or tissue damage. It is non-specific in about 90% of cases [4]. Study conducted in a Pakistani Tertiary Care Hospital showed that most of the LBP patients are the ones in the 21–40 years old age group. The study highlighted that the most frequent risk factors associated with LBP are hypertension, dyslipidaemia, history of lower back trauma, history of prolonged unsupported sitting, office workers using desks and healthcare environment. Additionally, LBP was also identified in women at home. In Pakistan, a woman is expected to do tiring house chores which involves hand washing clothes and dishes, cooking and cleaning all the house without any care given to posture or comfort. Physical inactivity, soft foam mattresses, smoking, drinking, heavy lifting, sleep disorders and anxiety were also found in association with LBP [5]. Nowadays, LBP has gained a significantly high attention in the Pakistani adult population, particularly among some occupations involving farmers, rickshaw drivers, office workers, teachers and textile workers. Effective management of LBP requires a comprehensive approach tailored to whether the pain is specific or non-specific. For non-specific LBP, combining physical therapy, psychological support, lifestyle changes, and careful use of medications can significantly improve outcomes. Comprehensive clinical assessment and a biopsychosocial approach are crucial, especially for chronic cases. Prioritizing non-pharmacological interventions and focusing on rehabilitation can help maintain independence and quality of life. Dear Editor, Low back pain (LBP) is not a disease itself, but it can be a sign of number of a number of conditions, such as pain near the midline, which can occasionally be localized sometimes, and occur between the inferior gluteal folds and costal margin, with or without referred leg pain [1,2]. The prevalence of LBP has been rising globally; According to recent studies Bangladesh, India, Nepal, Pakistan and Sri Lanka have rates of 64.8%, 19.8%, 69.5%, 40.6% and 36.2% respectively [3]. LBP can be categorised as either non-specific or specific. Non-specific means that the experience of pain cannot be confidently accounted for by another diagnosis such as an underlying disease, pathology or tissue damage. It is non-specific in about 90% of cases [4]. Study conducted in a Pakistani Tertiary Care Hospital showed that most of the LBP patients are the ones in the 21–40 years old age group. The study highlighted that the most frequent risk factors associated with LBP are hypertension, dyslipidaemia, history of lower back trauma, history of prolonged unsupported sitting, office workers using desks and healthcare environment. Additionally, LBP was also identified in women at home. In Pakistan, a woman is expected to do tiring house chores which involves hand washing clothes and dishes, cooking and cleaning all the house without any care given to posture or comfort. Physical inactivity, soft foam mattresses, smoking, drinking, heavy lifting, sleep disorders and anxiety were also found in association with LBP [5]. Nowadays, LBP has gained a significantly high attention in the Pakistani adult population, particularly among some occupations involving farmers, rickshaw drivers, office workers, teachers and textile workers. Effective management of LBP requires a comprehensive approach tailored to whether the pain is specific or non-specific. For non-specific LBP, combining physical therapy, psychological support, lifestyle changes, and careful use of medications can significantly improve outcomes. Comprehensive clinical assessment and a biopsychosocial approach are crucial, especially for chronic cases. Prioritizing non-pharmacological interventions and focusing on rehabilitation can help maintain independence and quality of life.